Dynamics of Religious Social Movements: A Case Study of the Fardu Kifayah Al-Mujahidin Group in Singaraja - Muiz, Ahmad Firdaus Rofiul; Margi, I Ketut; Syahrin, Alif Alfi (Universitas Tanjungpura, 2026)
The Al-Mujahidin Fardu Kifayah Group in Singaraja is a religious social movement that emerged within Bali’s Muslim minority community, specifically in response to the need for group participation in the handling of the deceased. The study’s objective is to comprehend the group’s organizational dynamics, historical background, and function in fostering social cohesion within the Muslim community. The study employed a qualitative case study methodology with purposive and snowball sampling techniques; information was gathered through participatory observation, in-depth interviews, and document analysis; the Miles and Huberman model was then used for interactive analysis. The findings demonstrated how this group developed from a straightforward study group into an organized organization with articles of association, technical task division, and quick coordination methods via WhatsApp groups and direct communication. In order to sustain service sustainability, the organization also offers training and member regeneration, though consistent participation is still difficult. The group was able to function as a solidarity network that enhanced the cohesiveness of the Muslim community within a multicultural society because of the strong social solidarity that developed through cooperative work during times of death, nondiscriminatory services, and social support for bereaved families. In conclusion, Fardu Kifayah Al-Mujahidin not only functions as a ritual institution but also as a form of religious organisational adaptation that maintains the continuity of social solidarity in a pluralistic environment.